BOOK REVIEW: PAUL B. ARMSTRONG, “STORIES AND THE BRAIN: THE NEUROSCIENCE OF NARRATIVE”, BALTIMORE, JOHN HOPKINS UNIVERSITY PRESS, 2020, 259 P. - Ada BELEUŢĂ (Studia Universitatis Babeş-Bolyai. Philologia, 2021)
The position that Paul B. Armstrong’s Stories and the Brain: The Neuroscience of Narrative finds within the fields of poststructuralist and postcognitive narratology is particularly interesting. While it makes considerable contributions to the collective efforts of establishing an interdisciplinary dialogue between cognitive sciences and the humanities, it does – at the same time, engage in an emphatic critique of similarly oriented theories of narrative. Even though he acknowledges the general shift from a computational model of the mind to “the 4e (embodied, enactive, embedded, and extended) view of cognition” (15), he denounces their lack of synchronization with recent neuroscientific findings on language, cognition, emotion, or narrative comprehension. To him, it appears that, “in their zeal to reject a Cartesian splitting of mind and body” (5), narratologists tend to overlook brain-based research in order to draw instead on psychological or philosophical perspectives.